Lubricants for the main components of pellet presses - Komar, Artem; Комар, Артем Станіславович (Запоріжжя: ТДАТУ, 2025)
Wood is becoming increasingly important as a fuel worldwide. Wood pellets are considered a true replacement for fossil fuels. Both private and public entities are increasingly switching to the use of wood pellets for heating as a substitute for petroleum products, a trend supported and encouraged by European governments.
Keywords: Lubricants; pellet presses